Oxyuris spp. Infection in Green Iguana (Iguana iguana) Under Different Cage Types - kusumarini , shelly; Rafi Dzakir Ghalib; Garvasilus Privantio Tegar Virgiawan Huler; Reza Yesica; Nanis Nurhidayah; Haris Muhamad; Nuha Fairusya (Universitas Airlangga, 2024)
The caging system becomes one of the most crucial points in the green iguana (Iguana iguana) husbandry practice since some pathogens are transmitted through ingesting contaminated feed or water in the cage. One of the most common health problems in the green iguana is caused by infection of the gastrointestinal nematode (GIN), Oxyuris spp. Here, we conducted a study to identify Oxyuris spp. infection in the green iguana under different cage types in Malang Raya, East Java. A total of 40 fecal samples were collected and examined through flotation and modified McMaster techniques from three cage types, namely loose cage / extensive (n= 7), terrarium (n= 13), and iron-based cage (n= 20). The results showed that all green iguanas are infected with Oxyuris spp. (40/40 or 100 % prevalence). The highest mean egg per gram (EPG) was found in the green iguana which kept in a loose cage / extensive (mean EPG [CI 95 %] = 14 799.21 [14 442.05 – 15 156.37]), followed by terrarium (mean EPG [CI 95 %] = 8 763.80 [8 436.30 – 9 091.30]), and iron-based cage (mean EPG [CI 95 %] = 1 433.42 [1 303.79 – 1 563.05], respectively. At the same time, there is a significant relationship (P<0,05) between the type of cage and the infection rate of Oxyuris spp. According to this result, we recommend an iron-based cage with routine daily cleaning as prevention for Oxyuris spp. infection among the green iguana.